The costs of shareholder activism: Evidence from a sequential decision model - Gantchev, Nickolay (Journal of Financial Economics, 2013)
This paper provides benchmarks for monitoring costs and evaluates the net returns to shareholder activism. I model activism as a sequential decision process consisting of demand negotiations, board representation, and proxy contest and estimate the costs of each activism stage. A campaign ending in a proxy fight has average costs of $10.71 million. I find that the estimated monitoring costs reduce activist returns by more than two-thirds. The mean net activist return is close to zero but the top quartile of activists earns higher returns on their activist holdings than on their non-activist investments. The large-sample evidence presented in this paper aids in understanding the nature and evolution of activist engagements.